Implementasi Metode Toilet Training dalam Menumbuhkan Kemandirian Anak Usia Toddler di Kelompok Bermain - Inayah Nurbaiti; Wulandari, Retno; Fahmi, Fahmi (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
According to the Indonesian Ministry of Health 2018, there are 23,729,583 children under the age of 0-4 years in Indonesia. According to the National Household Health Survey (SKRT), approximately 75 million preschool-aged children have difficulty controlling urination and defecation. In 2014, only 20% of children were successful in toilet training and 75% of children failed in toilet training. In preschool children aged 4-5 years who successfully completed toilet training, 40% and 60% respectively. Children's willingness to use the toilet affects their ability to use the toilet. This article describes the introduction and implementation of toilet training methods to encourage toddler independence in playgroups. This study aims to describe the implementation of toilet training in toddler independence education in playgroups. The method used in this research is field research with a qualitative descriptive approach. Data sources come from interviews with parents, teachers and observations of toddler-age children in playgroups. Application and implementation of toilet training methods to encourage the independence of toddler-age children in playgroups. The implementation of toilet training begins with planning story material from storybooks with the topic of toilet operations prepared, the implementation is carried out by the teacher in accordance with the habituation method and the story method and the evaluation, namely. the teacher gives assignments to children in the form of practicing toilet training related activities directly.